The U.S. in Syrian Conflict: A Critical Discourse Study on BBC International and BBC Indonesia Articles - Safitri, Alfiani (2014)
This present research examined the representation of United States in Syrian conflict as evidenced in BBC International and BBC Indonesia articles by using van Dijk's sociocognition framework (2009a & 2009b). This research employed qualitative method to describe the representation and its significance. The collected data were 5 online articles from BBC International and 5 online articles from BBC Indonesia. The data were analyzed in the unit of words, phrases, and sentences to reveal the representation of U.S. in Syrian conflict. This research disclosed that, according to the text, U.S. was represented as the Globo-cop, who controlled the plot in Syrian conflict. The representation was indicated by three indicators, namely: U.S. as a firm and powerful country, U.S. as being intimate with Opposition, and U.S. as being the Opposition group helper. Hence, by sociocognition and context analysis, the research revealed that the thought of BBC International and BBC Indonesia was shaped by the culture of their owner. However, they were readers-oriented in delivering the news. Key words: critical discourse analysis, sociocognition, van Dijk, representation, translation media, Syrian conflict. Penelitian ini mengkaji representasi Amerika Serikat dalam konflik Suriah dalam Artikel BBC Internasional dan BBC Indonesia dengan menggunakan bingkai sosiokognisi Van Dijk (2009a & 2009b). Penelitian ini menggunakan metode kualitatif untuk menjelaskan representasi dan makna dari representasi tersebut. Data yang terkumpul adalah 5 artikel daring dari BBC Internasional dan 5 artikel daring dari BBC Indonesia. Data tersebut dianalisis dalam unit kata, frasa, dan kalimat untuk mengungkap representasi A.S. dalam konflik Suriah. Penelitian ini menemukan bahwa, berdasarkan pada teks, A.S. direpresentasikan sebagai Globo-cop, yang mengontrol alur konflik Suriah. Representasi tersebut didukung oleh tiga indicator, yaitu: A.S. sebagai negara tegas dan berkuasa, A.S. sebagai pihak yang dekat dengan kelompok Oposisi, dan A.S. sebagai pihak yang membantu kelompok Oposisi. Lalu, berdasarkan analisis sosiokognisi dan konteks, penelitian ini menunjukkan bahwa pemikiran BBC Internasional dan BBC Indonesia dibentuik oleh kultur pemilik kedua agensi tersebut. Akan tetapi, keduanya menganut readers-oriented dalam menyampaikan berita. Kata kunci: Analisis Wacana Kritis, sosiokognisi, van Dijk, representasi, media terjemahan, konflik Suriah